Comparison of the Efficacy of Partial Inferior Turbinectomy and Submucosal Diathermy on Nasal Obstruction in Allergic Rhinitis (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to compare the effects of bilateral partial inferior turbinectomy and sub-mucosal diathermy of inferior turbinates on nasal obstruction in patients with allergic rhinitis.Study Design: Prospective comparative studyPlace and Duration of Study: This study was conducted at Departments of ENT, Mufti Mehmood Memorial (MMM) Teaching Hospital and District Headquarter Teaching Hospital (DHQ), Lakki Marwat from January 2009 to June 2013.Materials and Methods: Subjects of either sex, aging more than 10 years with symptomatic bilateral enlarged inferior turbinates due to allergic rhinitis attending ENT OPD were included. They were divided into two groups. An alternate sequential entry was made to group A and group B. Patients in group A were offered bilateral partial inferior turbinectomy (PIT) while those in group B underwent mono-polar sub-mucosal diathermy (SMD) of inferior turbinates. Data was collected at first visit prior to intervention, second at 1 month and third at 3 months after surgery. Anterior rhinoscopy and visual analogue scale were used to assess treatment outcomes.Results: Out of 96 patients with 48 patients in each group, males (58%.3) out-numbered the females (41.7%) in both groups. Mean age of the patients in group 1 was 21.88±7.528 range (10-35) years and in group 2 was a 19.75±6.525 range (10-33) year. The mean nasal obstruction score was lower in group 1 than in group 2 at 1 month, and 3 months after surgery suggesting a good outcome, although statistically non-significant (p=value 0.177, 0.198 respectively).Conclusion: Both bilateral PIT as well as SMD are effective in improving nasal obstruction in patients with hypertrophied inferior turbinates due to allergic rhinitis.